A Aviação Naval na Revolução de 1932 - Carlos Roberto Carvalho Daróz (Navigator)
On July 9, 1932, a political-military movement broke out in São Paulo as opposed to Getúlio Vargas’s provisional government. To deal with the rebellion, army troops and navy units were employed, which, after 85 days of fighting, managed to stifle the movement. Among its operational means, the Brazilian Navy employed Naval Aviation, which, despite its limitations, contributed to the protection of the fleet and supported the operations of ground forces. This paper aims to discuss and analyze the role played by the naval force, as well as the impacts and legacy caused by its participation in the fight against the revolution.